Visualizing financial success: planning is key. (26th September 2014) - Bird, Carolyn L.; Şener, Arzu; Coşkuner, Selda
Abstract Recent economic troubles in the US and abroad highlight the importance of family financial capability, including an understanding of financial markets. Financial capability is the foundation for desired financial behaviours, such as saving, budgeting, using credit wisely and planning. Study participants, a subsample of respondents to a Turkish university financial literacy survey (n = 374), who reported uninterrupted income for a 3‐year period were grouped as 'planners' and 'non‐planners'. These groupings allowed examination of the relationships between planning, financial management decisions, and differential outcomes in daily household financial well‐being. The practice of preferred financial management behaviours was predictive of debt. This research makes a unique contribution to the literature, demonstrating the importance of uninterrupted income over income amount in support of the planning process. Findings of this study have implications for professionals in the family and consumer sciences field and other practitioners assisting consumers with improving financial management outcomes.